KELAYAKAN MAJALAH BIOLOGI SEBAGAI MEDIA PEMBELAJARAN SUBMATERI INTERAKSI DALAM EKOSISTEM KELAS X SMA/MA - Elsa Ferella; Titin Titin; Syamswisna Syamswisna (FKIP Universitas Tanjungpura, 2022)
The purpose of this research is to find out the feasibility of the biology magazine as the teaching media in sub material interaction in ecosystem for sophomore in high school. This study used research and development (R&D) with the Plomp model. Feasibility test on the biology magazine which display the result of phase one validated by five validator consist of three lecturer and two sophomore teachers in class X from SMA Negeri 1 Sambas and SMA Negeri 1 Subah were selected by purposive. Validation assessment uses a Likert scale and data analysis uses the formula Lawshe (1975). The aspects assessed from the Biology magazine are aspects of language, content, and construction with 22 assessment criteria. The result of the biology magazine as teaching media acquire score 0,99 in CVI (Content Validity Index) which declared as a valid teaching material in sub material interaction in ecosystem for sophomore in highchool.